Optical calibration of the SNO+experiment and sensitivity studies for the neutrinoless double beta decay - Inácio, Ana Sofia Carpinteiro (2018)
Tese de mestrado, Física (Física Nuclear e Partículas) Universidade de Lisboa, Faculdade de Ciências, 2017